1985
DOI: 10.1017/s0094837300011477
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary implications of predation on Recent comatulid crinoids from the Great Barrier Reef

Abstract: Diving investigations of Recent comatulid crinoids at Lizard Island, Great Barrier Reef, indicate that, contrary to long-held notions, crinoids are subject to predation, principally by fishes of several families. Predation usually occurs as sublethal damage to the visceral mass and arms, from which the crinoids usually recover by regeneration. Aspects of the life habits, morphology, biochemistry, and physiology of comatulids are postulated to be adaptations that enable comatulid crinoids to resist predation. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
97
0
1

Year Published

1989
1989
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(99 citation statements)
references
References 29 publications
1
97
0
1
Order By: Relevance
“…With few exceptions (Clements 1988, Clements et al 1988, Dobson et al 1991, studies of ophiuroids have dealt only with arm regeneration. Meyer (1985Meyer ( , 1988 showed that crinoids may lose portions of the visceral mass to predators. Meyer (1988) studied regeneration of the visceral mass.…”
Section: Discussionmentioning
confidence: 99%
“…With few exceptions (Clements 1988, Clements et al 1988, Dobson et al 1991, studies of ophiuroids have dealt only with arm regeneration. Meyer (1985Meyer ( , 1988 showed that crinoids may lose portions of the visceral mass to predators. Meyer (1988) studied regeneration of the visceral mass.…”
Section: Discussionmentioning
confidence: 99%
“…IWP comatulid crinoids, for example, have higher incidences of spinose arm bases than do species in the WA. This difference is presumably related to partial predation by fishes (Meyer & Macurda 1977, Meyer 1985.…”
Section: Grazing and The Architecture Of Sessile Organismsmentioning
confidence: 99%
“…The only available studies are very old and incomplete [22][23][24]. In spite of this, the common presence in nature of partially or completely eviscerated specimens and individuals with visceral regeneration in progress [7,[25][26][27][28], indicates that the internal organs of crinoids display striking regenerative capabilities. Thus, we re-explored visceral regeneration using a modern approach in preliminary pilot studies, wich provided encouraging results [29,30].…”
Section: Introductionmentioning
confidence: 99%